Comparative Study on Dual and Triple Therapy Using Oral Antidiabetic Drugs in Treatment of Type 2 Diabetes Mellitus - Shakya, Sangita; Bajracharya, Smrity; Shakya, Amit; Shakya, Santosh; Chaudhary, Shailendra; Gautam, Suraj; Shankar, Ravi (Journal of Advanced Academic Research, 2017)
Introduction: Type 2 diabetes mellitus is a progressive complex disorder so most patients require dual and triple therapy using glucose- lowering agents.Purpose: To find the effectiveness of the dual therapy [glimepiride and metformin] and triple therapy [glimepiride, metformin and pioglitazone] for glycemic control.Method: The prospective study was conducted in Diabetes and Endocrinology Centre including 112 patients with Type 2 diabetes treating with oral antidiabetic drugs. Patients, age group between 30-70 years having pre- prandial blood glucose [≥ 110 mg/dl] and post-prandial blood glucose [≥ 140 mg/dl] were included. They were grouped into dual and triple therapy according to treatment they received. The blood glucose level was examined after one week of initial drug therapy. Patients taking oral antidiabetic drugs along with insulin therapy were excluded.Result: Type 2 diabetes mellitus was prevalent in the age group between 50- 60years. The reduction in pre-prandial blood glucose with dual therapy and triple therapy were 26.5 % and 27.1 % respectively and reduction in post-prandial blood sugar were 32.6 % and 30.5 % respectively. Hence the effectiveness of the dual therapy (p=0.827) and triple therapy (p=0.949) was similar in pre and post glycemic control .Conclusion: The dual and triple therapy may be equally effective for the treatment of type 2 DM.Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 128-137